Analisis Kemampuan Komunikasi Matematika dalam Materi Statistika Kelas VIII SMP Negeri 2 Jatiroto - Setianingsih, Eli; Susanto, Herry Agus; Farahsanti, Isna (Absis: Mathematics Education Journal, 2023)
This study aims to describe the mathematical communication skills of eighth-grade students of SMP Negeri 2 Jatiroto in statistical material. This research is a qualitative research. The subjects of this study were students of class VIII E SMP Negeri 2 Jatiroto. Data collection techniques used in this study were tests and interviews. Data analysis techniques used are data reduction, data presentation, and drawing conclusions.  The results of this study, the subjects selected were 6 students with 2 subjects of high achievement, 2 subjects of moderate achievement, and 2 subjects of low achievement. With high achievement subjects meeting the 5 indicators of mathematical communication ability given, medium achievement subjects meeting 2 indicators of given mathematical communication skills, and low achievement subjects fulfilling 1 indicator of given mathematical communication skills. The conclusions of the study indicate that the mathematical communication skills of class VIII students of SMP Negeri 2 Jatiroto in statistical material are as follows: (1) students with high achievement have good mathematical communication skills, (2) students with moderate achievement have quite good mathematical communication skills, (3) students with low achievement have poor mathematical communication skills.